The weaner pig [ nutrition and management - Varley, M. A. [ (Mike A.)]; Wiseman, J. [ (Julian)] (CABI, 2001)
Developed from a British Society of Animal Science meeting, held in September 2000, this book brings together the scientific disciplines involved in the pre- and post- weaning biology of the piglet. It concentrates on topics such as: growth/development,nutrition, immunology/health, ethology, and the physical environment.